Collaborative Organizational Learning (OL) Environment Through Email System : The Socio-Technical Framework Approach - Abdul Karim, Mohamad (UTeM, 2009)
An information system or information and communication technology (IS/ICT)application can be a strategic vehicle to seize opportunities for creating knowledge-based management operation in the context of collaborative Organizational Learning (OL) environment. The evolution of IS/ICT has made possible of many innovations of telecommunication systems that enable people in an organization exchanging knowledge in such collaborative environment. One of the innovations is an electronic mail (email)that has become a communication tool for supportive management activities. This work aims at describing the email antecedent, analyzing the email characteristics, examining and developing a socio-technical email transactional framework. Email promises three aspects: first, the communication, collaboration and coordination (3Cs) as email push-pull threading phenomena; second, the primacy socio-technical aspect of human-computer interaction (HCI) and third, promoting collaborative OL. This literature on email usage has emphasized on the technological impact of business change toward better effective and efficient organizational performance. However, there are still gaps resulted from the email activities and transactions such as lack of focus, information overload and spamming. There are not many empirical studies on the usage of email technology. The main issues are on email system characteristics that have not been optimized. Email has been ignored, misused and abused. It has failed to provide evidence for promoting collaborative OL. Email users are unclear what they had learned through email usage. A multi perspective of socio-technical approach was adopted to explore the antecedent, behavior and consequences (ABC) and explain the socio-technical phenomena of the email users. There are three phases of the research methodology comprising survey, interviews and technical experimentation. Data collection of survey was done at UTeM and KYM respectively. Interviews and technical experimentation were performed at KYM. In specific, the results indicate that first, the email users were found to use email effectively for job related purposes but it was very much informally shaped by social process that occurred across all organizational levels. Second, the push nature of the job-related email content has less significance towards information and knowledge management, however the email threading is still a significant managerial-pulled in nature of job-related connectivity especially between peers. Third, email supports the collaborative working environment but it is not intentionally tailored to OL in concern.The technical work suggests a need for further research especially on technical determinism of the email content and threading nature.